Conducting Online Writing Exchange: A Reflection to Tell - Mushoffan Prasetianto; Rizkiana Maharddhika (English Department - University of Sultan Ageng Tirtayasa, 2020)
There have been many researches on online language learning, especially online writing. Yet, research describing a reflection after experimenting with online writing to students is still under-investigated. To fill this gap, this paper aimed to inform the reflection of the researchers for the last three years conducting online writing exchange. The reflections came from the researchers’ view and students' views regarding the writing exchange program. The research design was narrative inquiry. The data were garnered from the researchers’ experiences and students’ interviews. The results of reflection revealed Strengths, Weaknesses, Opportunities, and Threats (SWOT). The strengths are flip classroom, flexibility for the teacher, motivation to write, writing practice, and interaction. The weaknesses are able to write a post after the deadline, unaltered topics in stage, unavailable notification of reply, a difficult operationalized website, and a short deadline. The opportunities are adding other countries from other continents, extending the collaboration into a full semester, and adding online chat on the website. The threats are less active participation from students and less active buddy.